2014
DOI: 10.1155/2014/241010
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Characterization of the Performance of Fluid Pumps Based on a Wankel Geometry

Abstract: The performance of fluid pumps based on Wankel-type geometry, taking the shape of a double-lobed limaçon, is characterized. To the authors' knowledge, this is the first time such an attempt has been made. To this end, numerous simulations for three different pump sizes were carried out and the results were understood in terms of the usual scaling coefficients. The results show that such pumps operate as low efficiency (<30%) valveless positive displacements pumps, with pump flow-rate noticeably falling at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…For this study, all the simulations were carried out in ANSYS CFX v 15, which is a commercially available computational fluid dynamics (CFD) code. Details of the simulation setup, including the method for modelling the motion of solids immersed in a fluid flow field and calibration against experimental data can be found in [15] and are not repeated here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, all the simulations were carried out in ANSYS CFX v 15, which is a commercially available computational fluid dynamics (CFD) code. Details of the simulation setup, including the method for modelling the motion of solids immersed in a fluid flow field and calibration against experimental data can be found in [15] and are not repeated here.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, the gross performance of Wankel pumps has been characterized by Wan et al [15] in terms of pump scaling coefficients; and, in essence, it was demonstrated that it operates as a low efficiency (<30%), valveless positive displacement pump. It was also found that internal flow field is rich in 3D vortices.…”
Section: Introductionmentioning
confidence: 99%
“…In other instances, external energy or force is applied to perturb the sample species to encourage mixing through diffusion. A review of microfluidics mixing is given by Lee et al 1 Wan et al 2 had been investigating the use of Wankel-like pump in microfluidics applications. They found from CFD simulations that a 2-apex rotor turning at low speed in 1-lobe epitrochoid-shaped housing is able to generate vortices at low Reynolds number and hence has the potential to improve mixing.…”
Section: Background: the Microfluidics Mixermentioning
confidence: 99%
“…Here the student was introduced to a mathematical model that describes the perimeter (i.e. the trajectory of the rotor tips, Figure 1) of the Wankel-type geometry, which is known as an epitrochoid 6
Figure 1.The epitrochoid trajectory of the ( m = 2) two-apex rotor tip. (a) Nomenclature for the m = 2 epitrochoid parametric equations.
…”
Section: Basic Conceptsmentioning
confidence: 99%
“…(b) Locating the 'centre' of the m ¼ 2 Wankel geometry. (c) and (d) Illustrate snapshots of the displacement of the rotor centre relative to the 'centre' of the Wankel geometry and the linear 'sliding action' of the centre point along the slot (in the rotor) as the rotor rotates.an epitrochoid6…”
mentioning
confidence: 99%